THE EFFECT OF ASTRAGALUS EXTRACTIVE ON ALVEOLAR BONE REBUILDING PROGRESS OF TOOTH EXTRACTED SOCKET OF OVARIECTOMIED RATS - Liu, Xiaochen; Zhang, Runju; Zhou, Yi; Yang, Yanli; Si, Hongling; Li, Xiaohong; Liu, Li (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Postmenopausal osteoporosis (PMO) is an estrogen deficiency condition that causes severe loss of bone mass in the vertebrae and long bones. We explored the effect and the possible underlying mechanism of the extracts of Astragalus (AE) on the tooth alveolar bone rebuilding progress of postmenopausal osteoporosis of PMO animal models. Material and methods: The PMO models were acquired by ovariectomy. After 8 weeks the first left maxillary molars of the rats were extracted and AE was administered orally for 8 weeks. Then the histological morphology and the transcription and expression of TGF-β1 and TNF-α in the tooth extracted socket were detected by HE dying, QRT-PCR and ELISA. Results: The results showed that the new bone volume and TGF-β1 was significantly lower in PMO group than the control group and AE group at the observing period. At the same time TNF-α in PMO group was significantly higher than the other two groups. Moreover AE group had no significant differences with the control group in all data at the observing period. Conclusion: AE has positive effect on alveolar bone rebuilding progress of tooth extracted socket of PMO rats. AE also has the potential to enhance the expression of TGF-β1and decrease the expression of TNF-α of the rebuilding tooth extracted socket.